2005
DOI: 10.1097/01.mpa.0000153337.58105.47
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cancer Cell Metastasis Into the Pancreas

Abstract: Pancreatic metastasis from RCC is rare but can occur even more than 20 years after primary tumor manifestation. Our results show that pancreatic resections for metastasis can be performed safely with a low rate of complications. Patients with a history of RCC should undergo a long-term follow-up to detect and evaluate for pancreatic metastases as well for metastasis to other organ sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(51 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…It is interesting to note that a literature review by Wente et al found there to be a slight predilection for pancreatic metastasis from a left kidney primary (58%), although this left-sided predilection is not supported in all series. 11 Metastasectomy at the time of nephrectomy provides a survival benefit over nephrectomy alone for patients found to have synchronous, solitary metastatic lesions.31,35 Surgical options for pancreatic metastasis must be carefully planned and individualized to each patient. Resection must aim to achieve clear margins, while leaving as much healthy pancreatic parenchyma as possible.…”
mentioning
confidence: 99%
“…It is interesting to note that a literature review by Wente et al found there to be a slight predilection for pancreatic metastasis from a left kidney primary (58%), although this left-sided predilection is not supported in all series. 11 Metastasectomy at the time of nephrectomy provides a survival benefit over nephrectomy alone for patients found to have synchronous, solitary metastatic lesions.31,35 Surgical options for pancreatic metastasis must be carefully planned and individualized to each patient. Resection must aim to achieve clear margins, while leaving as much healthy pancreatic parenchyma as possible.…”
mentioning
confidence: 99%
“…[7] The longest period between the primary cancer and the development of pancreatic metastasis was 15-22 years. [5,8] In the present study, the longest period was 27 years. Wente et al, suggest that the follow-up period in patients with early-stage RCC should extend beyond 20 years for the detection of recurrence or metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Wente et al, suggest that the follow-up period in patients with early-stage RCC should extend beyond 20 years for the detection of recurrence or metastatic disease. [8] The current approaches to the treatment of metastatic RCC include immunotherapy with interferon-α, targeted therapy, or one of these therapies combined with metastatectomy. Motzer et al, reported that the median progression-free survival with interferon-α was 5 months and the response rate was 6%.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature data, left renal tumors result more often pancreatic metastases. [9] The already developed metastases are slow-growing, and if they are resectable, the 5-year survival rate is more than 50%. [3] In non-small cell lung cancer, pancreas metastasis is more commonly a part of multi-organ metastases.…”
Section: Discussionmentioning
confidence: 99%